Del corazón del trópico a la amable Ginebra - Llorca Antolín, FIna (Revista de Filología Románica, 2006)
Aurora Bertrana (Girona, 1982-Berga, 1974) is well-known for her works about Pacific Islands and her «journey impressions» which relate her stay in Spanish Morocco. But is Geneva that she chooses, her city. Other Swiss towns inspire her writing, marked by travelling and adventure: Swiss mountains and the village of Etobon give her the materials for maturity novel Entre dos silencis («Between Two Silences»).